On immunity an inoculation - Eula,Biss. (Minneapolis Graywolf Press, 2015)
Reflecting on her own experience as a new mother, Biss investigates the metaphors and myths surrounding our conception of immunity and its implications for the individual and the social body. She extends a conversation with other mothers to meditations on Voltaire's Candide, Bram Stoker's Dracula, Rachel Carson's Silent Spring, Susan Sontag's AIDS and Its Metaphors, and beyond. On Immunity is an inoculation against our fear and a moving account of how we are all interconnected our bodies and our fates.
Includes bibliographical references (pages 191-202).
Keywords: Biss, Eula--Family.